Measuring the Cytochrome c Nitrite Reductase Activity—Practical Considerations on the Enzyme Assays - Célia M. Silveira; Stéphane Besson; Isabel Moura; José J. G. Moura; M. Gabriela Almeida (Bioinorganic Chemistry and Applications)
The cytochrome c nitrite reductase (ccNiR) from Desulfovibrio desulfuricans ATCC 27774 is able to reduce nitrite to ammonia in a six-electron transfer reaction. Although extensively characterized from the spectroscopic and structural points-of-view, some of its kinetic aspects are still under explored. In this work the kinetic behaviour of ccNiR has been evaluated in a systematic manner using two different spectrophotometric assays carried out in the presence of different redox mediators and a direct electrochemical approach. Solution assays have proved that the specific activity of ccNiR decreases with the reduction potential of the electronic carriers and ammonium is always the main product of nitrite reduction. The catalytic parameters were discussed on the basis of the mediator reducing power and also taking into account the location of their putative docking sites with ccNiR. Due to the fast kinetics of ccNiR, electron delivering from reduced electron donors is rate-limiting in all spectrophotometric assays, so the estimated kinetic constants are apparent only. Nevertheless, this limitation could be overcome by using a direct electrochemical approach which shows that the binding affinity for nitrite decreases whilst turnover increases with the reductive driving force.